Effects of daily consumption of psyllium, oat bran and polyGlycopleX on obesity-related disease risk factors: A critical review - Jane, M.; McKay, J.; Pal, Sebely (Emerald Group Publishing, 2019)
© 2019 The persistent obesity crisis, with its increased risk for the metabolic syndrome (MetS), type 2 diabetes, and cardiovascular disease (CVD), continues to damage the health of populations globally, including children. Diets rich in the fiber provided by fruit and vegetables support good metabolic health, although few adults and children achieve the recommended daily target. Daily fiber supplementation, particularly with soluble fiber products, such as psyllium, oat bran, or a newer product such as PolyGlycopleX, may provide a convenient solution. Literature searches were conducted to identify original research articles, systematic reviews, and meta-analyses with the search terms psyllium, oat bran, PolyGlycopleX, and PGX, AND adults and children AND overweight, obesity, and metabolic syndrome. Data source was Embase and PubMed from 1980 to 2017. The results show that the addition of a soluble fiber product, most notably psyllium, improves blood lipid profiles, particularly total and low-density lipoprotein cholesterol, as well as glycemic response, and increases satiety, and by thus improving MetS and CVD risk factors, may augment the processes initiated by weight reduction diets. Although less studied than psyllium, the available evidence has shown that ß-glucan present in oat bran has a beneficial effect on MetS and CVD risk factors, particularly blood lipids and glycemia. Early research has found PolyGlycopleX to provide similar benefits to other soluble fiber products, and suggest it may also assist with weight loss. This critical review demonstrates that soluble fiber supplements used as an adjunct to dietary and lifestyle modifications may assist with the treatment of CVD and MetS risk factors. More research is needed to further clarify the benefits of PolyGlycopleX in particular, as well as to develop safe and efficacious recommendations for fiber supplementation of all types for children in general.